Pengaruh financial distress, koneksi politik, capital intensity, leverage dan ukuran perusahaan terhadap tax aggressiveness - Qalbi, Andi Batari Nurul; Asmara, Rina Yuliastuty (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study was conducted to examine the effect of financial distress, political connections, capital intensity, leverage, and firm size on tax aggressiveness (in manufacturing companies in the basic industrial sector and chemicals listed on the Indonesia Stock Exchange for the period 2018–2020). This study uses 69 samples from the financial statements of manufacturing companies in the basic industrial sector and chemicals listed on the IDX for the period 2018-2020. The sample in this study was determined through a non-probability sampling technique with a purposive sampling method. This study uses an explanatory research type with a quantitative approach with the SPSS 26 program. The results of this study are that Financial Distress and Capital Intensity have a positive and significant effect on Tax Aggressiveness, while Political Connections, Leverage, and Company Size have no effect on Tax Aggressiveness.